Restraints on access to news and information / Baru Bian - Bian, Baru (1984)
This paper is written in partial fulfilment of the requirement for the Diploma In Law course offered at the Institute of Technology MARA, Shah Alam. The paper focuses upon one key aspect of freedom of the Press, the right of access and its restraints and limitations. This issue which has just cropped up in Malaysian purview has raised some legal questions. The problem is highlighted in juxtaposition with the situation currently existing in England and the United States. I am most grateful to Mr. U.K. Me non, the Go—ordinator of the School of Administration and Law, Institute of Technolog MARA, Shah Alam, who has helped me to narrow and define the object of this paper and who has constantly supervised me to its completion. Errors and omissions are of course entirely min